THE EVOLUTION OF TERRORISM IN THE INTERNET SPACE AS A SECURITY CHALLENGE (Security Dialogues, 2024)
Although a universally accepted definition of terrorism does not yet exist, almost all researchers of this phenomenon agree that it has existed since ancient times, evolves and very skillfully adapts to the new digital age. Terrorist organizations began to feel the benefits of the Internet as soon as it appeared, especially in fast communication, which, although at first it seemed not so secure, later with the help of the encrypted platforms developed by terrorist organizations, communication not only which has become much safer, but it has given even more courage to sympathizers to join the terrorist cause and make their contribution, whether they be the so-called “worker bees” (mujaheddin/mujaheddin - the diligent ones), or join the battlefields. This paper aims to highlight how terrorists use the benefits of the developed technology especially the internet. One of the things that emerges as a challenge is precisely the role that women play in recruitment and radicalization for terrorist organizations. Namely, a woman seems to go beyond the conservative treatment in the regions where terrorism is present. Thus, terrorism begins to use all possible resources available to it. Children also become apotential target for recruitment mostly in the internet space, but also in the gaming world. Like the uneven distribution of goods, the power struggle of the great powers, and at the end of the day, systemic inequality contributes to terrorism still being treated as one of the biggest security threats in the global world.